Association between the BDNF Val66Met polymorphism and major depressive disorder: a systematic review and meta-analysis - Wang, Yuxia; Li, Ou; Li, Nana; Sha, Zhongwei; Zhao, Zhenghao; Xu, Jian (Frontiers in Psychiatry, 2023)
Abstract Study Objectives: This meta-analysis analytically reviewed recent studies concerning potential associations between the Brain-Derived Neurotrophic Factor(BDNF) Val66Met polymorphism and susceptibility to Major Depressive Disorder(MDD) , with subgroup analyses for race and age. Methods: Relevant case-control studies were systematically searched in PubMed, Embase, Web of Science, China national knowledge infrastructure（CNKI）, Wanfang and Sinomed databases. A total of 24 studies were finally identified to have reported outcomes including alleles, dominant genes, recessive genes, homozygosity and heterozygosity. Subgroup meta-analyses were performed based on participant age and ethnicity. Publication bias was represented by funnel plots. All meta-analyses of the randomized controlled trials included for evaluation were performed using RevMan5.3 software. Results: Findings revealed no significant association between the BDNF Val66Met polymorphism and MDD. However, the Met allele was found to be associated with genetic susceptibility to MDD among whites on subgroup analysis (OR=1.25, 95% CI: 1.05-1.48, P=0.01). In the genetic model, dominant (OR=1.40, 95% CI: 1.18-1.66, P=0.0001), recessive (OR=1.70, 95% CI: 1.05-2.78, P=0.03) and homozygous (OR=1.77, 95% CI: 1.08-2.88, P=0.02) genes were all associated with MDD. Conclusions: Despite outcome limitations, this meta-analysis confirmed that the BDNF Val66Met polymorphism is a susceptibility factor for MDD in white populations.